Advertising values and Beauty ideals: A content analysis from 1930s to 1940s of No.7 printed advertisements. - yang, deng (2016)
Being beautiful has become increasingly important to women. People can become more beautiful by using cosmetics and skincare products. In contrast, advertising is a very effective medium that propagandises beauty related products. It is meaningful to research how advertisements convey values and beauty ideals. No.7 as a cosmetics and skin-care brand that produces beauty related products is the object of study. By studying ads of this brand from 1930s to 1940s, the paper draws a conclusion that advertisement values and beauty ideals are largely determined by the social background and brand positioning.